Solanum nigrum Linn.: An Insight into Current Research on Traditional Uses, Phytochemistry, and Pharmacology - Chen, Xufei; Dai, Xufen; Liu, Yinghai; Yang, Yan; Yuan, Libang; He, Xirui; Gong, Gu (Frontiers in Pharmacology, 2022)
Solanum nigrum Linn., is a common edible medicinal herb of the Solanaceae family which is native to Southeast Asia and is now widely distributed in temperate to tropical regions of Europe, Asia, and America. Traditionally, it has been used to treat various cancers, acute nephritis, urethritis, leucorrhea, sore throat, toothache, dermatitis, eczema, carbuncles, and furuncles. Up to now, 188 chemical constituents have been identified from S. nigrum. Among them, steroidal saponins, alkaloids, phenols, and polysaccharides are the major bioactive constituents. Investigations of pharmacological activities of S. nigrum revealed that this edible medicinal herb exhibits a wide range of therapeutic potential, including antitumor, anti-inflammatory, antioxidant, antibacterial, and neuroprotective activities both in vivo and in vitro. This article presents a comprehensive and systematic overview of the botanical, traditional uses, phytochemical compositions, pharmacological properties, clinical trials, and toxicity of S. nigrum to provide the latest information for further exploitation and applications of S. nigrum in functional foods and medicines.